EFEKTIVITAS MAGGOT (HERMETIA ILLUCENS) SEBAGAI PAKAN LELE DENGAN METODE BUDIKDAMBER - Aditya Teguh Kurniawan; Agustin (Jurnal Agroekoteknologi dan Agribisnis, 2025)
Black soldier fly (BSF) maggots (Hermetia illucens) produced from organic waste have potential as an alternative feed ingredient in an integrated catfish-bok choy bucket culture system. This study aims to optimize maggot rearing substrates and to evaluate catfish growth and bok choi yield in an integrated cultivation system under partial or total substitution of commercial pellets with maggots. The study was conducted from September 2022 to March 2023 at the Agroecotechnology Experimental Farm, Trilogi University, Jakarta. Two experiments were performed, each arranged in a single-factor randomized complete block design. The first experiment identified the best maggot rearing substrate using four treatments: rice residue, vegetable waste, coconut residue, and a mixed substrate (rice residue + vegetable waste + coconut residue). The best-performing substrate from Experiment 1 was then used for maggot production in Experiment 2. The second experiment assessed the effectiveness of maggots as catfish feed in cultivation system by comparing three feeding treatments (pellets, maggots, and a 50:50 pellet–maggot mixture) across three bok-choy cropping periods. The mixed substrate was the best rearing medium for the maggot growing phase. Replacing pellets with maggots at 50% and 100% did not significantly affect harvested catfish length and weight and did not reduce bok-choy yield in the integrated cultivation system.